Transdermal delivery of allopurinol-loaded nanostructured lipid carrier in the treatment of gout - Zakir Ali; Fakhar ud Din; Fatima Zahid; Saba Sohail; Basalat Imran; Salman Khan; Maimoona Malik; Alam Zeb; Gul Majid Khan (BMC, 2022)
Abstract Background Allopurinol (ALP), a xanthine oxidase inhibitor, is a first line drug for the treatment of gout and hyperuricemia. Being the member of BCS class II drugs, ALP has solubility problem, which affects its bioavailability. Also, ALP has shorter half-life and showed GI related problems. In present study, ALP was encapsulated in nanostructured lipid carriers (NLCs) to ensure enhanced bioavailability, improved efficacy and safety in vivo. Methodology ALP-loaded NLCs were fabricated by micro-emulsion technique. The prepared NLCs were optimized via design expert in term of particle size, zeta potential and entrapment efficiency. FTIR, PXRD and TEM analysis were carried out to check chemical interaction, polymorphic form and surface morphology of the optimized formulation. ALP-loaded NLCs were then loaded into HPMC based poloxamer-407 gel and were characterized. In vitro and ex vivo analysis were carried out via dialysis membrane method and franz diffusion cell, respectively. Uric acid was used for induction of gout and the anti-gout activity of ALP-loaded NLCs gel was performed and compared with ALP suspension. Results The optimized formulation had particles in nano-range (238.13 nm) with suitable zeta potential (-31.5 mV), poly-dispersity index (0.115) and entrapment of 87.24%. FTIR results confirmed absence of chemical interaction among formulation ingredients. XRD indicated amorphous nature of ALP-loaded NLCs, whereas TEM analysis confirmed spherical morphology of nanoparticles. The optimized formulation was successfully loaded in to gel and characterized accordingly. The in vitro release and drug release kinetics models showed sustained release of the drug from ALP-loaded NLCs gel. Furthermore, about 28 fold enhanced permeation was observed from ALP-loaded NLCs gel as compared to conventional gel. Skin irritation study disclosed safety of ALP-loaded NLCs gel for transdermal application. Furthermore, ALP-loaded NLCs gel showed significantly enhanced anti-gout activity in Sprague-Dawley rats after transdermal administration as compared to oral ALP suspension. Conclusion ALP-loaded NLCs gel after transdermal administration sustained the drug release, avoid gastrointestinal side effects and enhance the anti-gout performance of ALP. It can be concluded, that NLCs have the potential to deliver drugs via transdermal route as indicated in case of allopurinol.